2002
DOI: 10.1002/pd.308
|View full text |Cite
|
Sign up to set email alerts
|

Increased fetal nuchal translucency at 11–14 weeks

Abstract: Nuchal translucency (NT) is the sonographic appearance of a subcutaneous collection of fluid behind the fetal neck. The measurement of fetal NT thickness at the 11-14-week scan has been combined with maternal age to provide an effective method of screening for trisomy 21; for an invasive testing rate of 5%, about 75% of trisomic pregnancies can be identified. When maternal serum free-beta human chorionic gonadotrophin (beta-hCG) and pregnancy-associated plasma protein-A (PAPP-A) at 11-14 weeks are also taken i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
108
0
9

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(120 citation statements)
references
References 50 publications
0
108
0
9
Order By: Relevance
“…TTTS characterized by overgrowth of a recipient twin and undergrowth of the donor twin is attributed to vascular communication via placenta between twins (Wee and Fisk 2002;Nicolaides 2002;Crombleholme 2003). Polycytemia and anemia seen in case 4 are an example of TTTS, and to our knowledge, only one case of MC DZT with TTTS other than case 4 has been reported in the literature (Quintero et al 2003).…”
Section: Clinical Implications Of MC Placentamentioning
confidence: 93%
“…TTTS characterized by overgrowth of a recipient twin and undergrowth of the donor twin is attributed to vascular communication via placenta between twins (Wee and Fisk 2002;Nicolaides 2002;Crombleholme 2003). Polycytemia and anemia seen in case 4 are an example of TTTS, and to our knowledge, only one case of MC DZT with TTTS other than case 4 has been reported in the literature (Quintero et al 2003).…”
Section: Clinical Implications Of MC Placentamentioning
confidence: 93%
“…The NTM screens for DS in the first trimester of pregnancy and is done by ultrasound scanning. 22 The MST is a blood test in the second trimester of pregnancy ("triple-test") and screens for DS and NTDs. 23 Both prenatal screening tests provide an individualized risk estimation of having a child with one of these disorders, and thus identify a high-risk subgroup within a population of pregnant women.…”
Section: Settingmentioning
confidence: 99%
“…16 Possible mechanisms for increased NT are: cardiac failure in association with the abnormalities of heart and great arteries, venous congestion in the head and neck due to various reasons, altered composition of the extracellular matrix, abnormal or delayed development of the lymphatic system and also failure of the lymphatic drainage, fetal anemia or hypoproteinemia, congenital infection of the fetus etc. 17 Whatever the etiologies for fetal nuchal translucency are, measurement of nuchal translucency as a screening method has firmly taken place in practice. Our study has shown that NT measurement is effective in picking up the most of the cases.…”
Section: Discussionmentioning
confidence: 99%